2019
DOI: 10.1186/s13054-019-2628-x
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cell function and epigenetic expression evolves over time after surgical sepsis

Abstract: BackgroundSepsis is an increasingly significant challenge throughout the world as one of the major causes of patient morbidity and mortality. Central to the host immunologic response to sepsis is the increase in circulating myeloid-derived suppressor cells (MDSCs), which have been demonstrated to be present and independently associated with poor long-term clinical outcomes. MDSCs are plastic cells and potentially modifiable, particularly through epigenetic interventions. The objective of this study was to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 65 publications
9
64
1
1
Order By: Relevance
“…Overall, the present results provide robust complementary information to that recently published by Hollen and colleagues [3]. Indeed, we observed that the persistence of increased M-MDSC after 1 week was significantly associated with worsening.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Overall, the present results provide robust complementary information to that recently published by Hollen and colleagues [3]. Indeed, we observed that the persistence of increased M-MDSC after 1 week was significantly associated with worsening.…”
supporting
confidence: 89%
“…To the editor, Recent observations indicate that some septic patients, after inaugural inflammation, enter a stage of protracted immunosuppression that may take weeks/months to vanish and associate with increased rate of secondary infections and mortality [1]. Delayed elevation of myeloidderived suppressor cells (MDSC) has recently been hypothesized as a key mechanism sustaining sepsisinduced immunosuppression [2,3]. These cells constitute a heterogeneous population of immature myeloid cells characterized by their capacity to suppress T cell response [4].…”
mentioning
confidence: 99%
“…MDSCs will be recruited into inflamed tissues where they suppress acute inflammatory responses; however, long-term presence of MDSCs suppresses the host's immune system, and increases susceptibility to infection ( 43 ). Hollen observed that MDSCs kept elevating in sepsis survivors for at least 6 weeks after infection, but only MDSCs obtained 14 days and later post-sepsis had a significant suppressive function ( 44 ). In the current study, we counted the number of MDSCs in BM and spleen, and observed that the number of MDSCs from BM was small on day 1 post-CLP while increased significantly to a high level on day 3, which is considered entering the late stage of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…These specific genes are also important to the function of myeloid derived suppressor cells, which have been shown to be expanded and able to suppress T-cell function at Day 14 in septic patients. 35 Therefore, the gene signature seen in the both humans and mice at Day 14 appears to represent the continued expansion of immune cells secondary to a state of persistent low grade inflammation and immunosuppression after sepsis, especially in elderly patients whom are more likely to follow a clinical trajectory to CCI. 9,36 Interestingly, although this murine model of sepsis better recapitulates late human sepsis in mixed age cohorts, we found that the aged mice transcriptomic response to CLP + DCS still does not correlate better with the older adult human transcriptome after sepsis.…”
Section: Discussionmentioning
confidence: 99%